Children's exposure to psychological abuse and neglect: A population‐based study in rural Bangladesh. (20th May 2020) - Haque, Md Atiqul; Moniruzzaman, Syed; Janson, Staffan; Rahman, AKM Fazlur; Mashreky, Saidur Rahman; Eriksson, Ulla‐Britt
Abstract: Aim: We aimed to estimate the prevalence and risk factors of child psychological abuse and neglect in a rural area of Bangladesh. Methods: Data were obtained from interviewing 1416 children aged 11‐17 years administering the International Society for the Prevention of Child Abuse and Neglect Child Abuse Screening Tool for Children between March and April 2017. Linear regression analysis was used to estimate the risks of child psychological abuse and neglect. Results: The prevalence rates of at least one form of psychological abuse both in the past year and lifetime were more than 97 per cent. Moreover, the rates of at least one form of neglect were about 58 per cent during the past year and 78 per cent over lifetime. Living separately from parents posed children to significant risks of neglect and psychological abuse. Working children and greater number of siblings in a family were risk factors for neglect, whereas witnessing family violence and being bullied were risk factors for psychological abuse. Children with more years of schooling experienced less neglect and psychological abuse. Conclusion: The high prevalence of child psychological abuse and neglect in this study shows child maltreatment as an ignored issue in Bangladesh.